2012
DOI: 10.1038/cddis.2012.49
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Batf induces an apoptotic defect and an associated lymphoproliferative disorder in mice

Abstract: Activator protein-1 (AP-1) is a dimeric transcription factor composed of the Jun, Fos and Atf families of proteins. Batf is expressed in the immune system and participates in AP-1 dimers that modulate gene expression in response to a variety of stimuli. Transgenic (Tg) mice overexpressing human BATF in T cells were generated using the human CD2 promoter (CD2-HA (hemagglutinin antigen) - BATF). By 1 year of age, over 90% of the mice developed a lymphoproliferative disorder (LPD). The enlarged lymph nodes charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…disorder caused by increased T cell survival has been observed in aged mice overexpressing BATF (Logan et al, 2012). We observed that BATF KO CD4 + T cells were comparable BATF KO iT reg cells fail to suppress inflammation in the intestine As shown in Fig.…”
Section: Batf Ko Mice Are Defective In Forming Intestinal Foxp3 + Andsupporting
confidence: 67%
“…disorder caused by increased T cell survival has been observed in aged mice overexpressing BATF (Logan et al, 2012). We observed that BATF KO CD4 + T cells were comparable BATF KO iT reg cells fail to suppress inflammation in the intestine As shown in Fig.…”
Section: Batf Ko Mice Are Defective In Forming Intestinal Foxp3 + Andsupporting
confidence: 67%
“…51,52 Our transcriptomics data showed that ZnO NPs reduced the expression of genes implicated in the positive regulation of "immune response", "cell activation", "cell proliferation", "cell migration", "cell adhesion" and "signal transduction". For example, KIT, which is a key receptor whose signaling is essential for the activation, survival and proliferation of hematopoietic stem cells, 53,54 BATF, which plays significant roles in the survival and proliferation of blood cells, 55,56 and PTPRC, which is required for hemopoiesis and homing of leukemic cells to bone marrow, 57 were down-expressed following the treatment with ZnO NPs. Other interesting genes including IGF1, VEGFA and NCKAP1L, which promote the survival, proliferation and migration of cancer cells, [58][59][60][61][62][63][64] were also down-expressed in the treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, quantification of thymic iNKT cells in Batf ΔZ/ΔZ mice revealed a number equivalent to WT mice [2]. As the CD2-HA-BATF transgene directs BATF overexpression to all T cells (thymic and peripheral) [7], iNKT cells were re-examined and compared to numbers in WT and Batf ΔZ/ΔZ mice. The percentage of T cells positive for interaction with glycolipid-loaded CD1d tetramers was assessed by flow cytometry using single cell suspensions from thymus, spleen and PLN.…”
Section: Resultsmentioning
confidence: 99%
“…Batf ΔZ/ΔZ and CD2-HA-BATF mice expressing human, HA-tagged BATF were described previously [2,7] and were maintained by breeding to C57Bl/6 mice (Harlan, Indianapolis, IN). Experiments were performed using sex-matched littermates between 6 and 12 wk of age.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation